Analyzing the connection between gymnast's stature and medal performance in apparatuses in men's artistic gymnastics - Bagci, E. (Science of Gymnastics Journal, 2023)
In order to achieve success in sports, certain physical fitness characteristics are necessary. This study aims to determine whether a relationship exists between the height of male gymnasts who have won medals in the World Championships and Olympic Games in Artistic Gymnastics, and the apparatus on which they achieved those medals. Competitions in Men`s Artistic Gymnastics at World Championships and Olympic Games are held in six apparatuses for individuals: floor exercise, pommel horse, rings, vault, parallel bars and horizontal bar. Each apparatus follows specific rules for evaluating gymnastics routines. Airborne acrobatics dominate on floor and vault, while support holds prominence on pommel horse and parallel bars, and hanging manoeuvres characterize rings and the high bar. While a gymnast`s body height influences all forms of gymnastics, the question remains: who can rise to the top on each apparatus?